(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The study was carried out to investigate the ecotoxicity of Isoproturon on Lemna minor and the interaction of the EC50 value of the chemical with sorption behaviour of the chemical in soil. The sorption isotherms (Kf and KOC) for Isoproturon were determined for three different soils having various organic carbon and clay content. EC50 for Lemna was determined both with and without soil. Both the Freundlich adsorption coefficient (Kf) and normalized sorption coefficient (KOC) values varied with different types of soil. There was moderate correlation between the log Kf and log KOC existed. The regression study revealed a strong relationship between log KOC and organic carbon and between log KOC and soil clay content. There EC50 value for Lemna grown with soil was higher than that grown without soil. However, the difference was statistically insignificant. Greater degree of inconsistency in various data suggests the reiteration of the study. DOI: http://dx.doi.org/10.3329/ralf.v1i1.22347 Res. Agric., Livest. Fish.1(1): 13-18, Dec 2014